2012
DOI: 10.2166/wst.2012.385
|View full text |Cite
|
Sign up to set email alerts
|

Removal of volatile organic compounds by heterogeneous ozonation on microporous synthetic alumina silicate

Abstract: A hybrid process combining adsorption and ozonation was examined as an alternative treatment for odorous volatile organic compounds (VOCs). Methyl ethyl ketone (MEK) was chosen to study the influence of operating parameters. Two synthetic aluminosilicates (faujasite-Y and ZSM-5) were tested for adsorption and reactivity with ozone. The adsorption equilibrium measurement on both adsorbents showed that adsorption performance depends on temperature but is not sensitive to relative humidity, due to the hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Synthetic zeolites have been used to eliminate low concentrations of VOCs (butan-2-one and toluene) from contaminated streams, using a combined procedure (adsorption and ozonation) as alternative treatment. Regeneration of VOC-saturated zeolites was conducted by ozonation in order to achieve a complete mineralization of adsorbed organic compounds [7,8]. The use of magnesium-exchanged zeolites (Mn-Y, Mn-MOR, and Mn-ZSM-5) has been reported in the catalytic ozonation of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic zeolites have been used to eliminate low concentrations of VOCs (butan-2-one and toluene) from contaminated streams, using a combined procedure (adsorption and ozonation) as alternative treatment. Regeneration of VOC-saturated zeolites was conducted by ozonation in order to achieve a complete mineralization of adsorbed organic compounds [7,8]. The use of magnesium-exchanged zeolites (Mn-Y, Mn-MOR, and Mn-ZSM-5) has been reported in the catalytic ozonation of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic zeolites appear as alternative materials for gaseous ozone removal from contaminated streams, due to their high thermal and chemical stability. They have been applied as catalysts in advanced oxidation processes in combination with ozone for the oxidation of volatile organic compounds from industrial emissions [5][6][7]. Concerning to gaseous ozone abatement over zeolites at ambient conditions, there are only few reported investigations [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…VOC molecules tend to adsorb most strongly in areas where the pore diameter of the adsorbent is close to the molecular diameter of the VOCs. For instance, in a silicalite ZSM-5 with narrow pores of 5.5 Å diameter, the methyl ethyl ketone (MEK) molecules with a kinetic diameter of 5.2 Å interact strongly with the channel walls, whereas this interaction is much smaller in large pores of aluminosilicates such as de-aluminated faujasite Y (Fau-Y-7.4 Å) [69]. The effect of the porosity and the surface chemistry of ACs on the adsorption capacity of low concentrated VOCs (benzene and toluene) has been investigated by Lillo-Rodenas et al [70,71].…”
Section: Physical Properties Of Sorbent/catalystmentioning
confidence: 99%
“…For instance, Song et al demonstrated that the breakthrough time for the adsorption process was significantly reduced at elevated temperatures compared to room temperature indicating lower adsorption capacity [32]. Brodu et al have reported the influence of temperature on MEK adsorption capacity of two aluminosilicates (Fau-Y, ZSM-5) [69]. The quantity of adsorbed MEK on both Fau-Y and ZSM-5 decreased with increasing temperature.…”
Section: Temperaturementioning
confidence: 99%